Assyria to Iberia : at the dawn of the Classical Age - Aruz, Joan,; Graff, Sarah B.; Rakic, Yelena. (The Metropolitan Museum of Art, 2014)
"This comprehensive book explores the spectacular art of the first millennium B.C. from the Near East to Western Europe. This was the world of Odysseus, in which trade proliferated with Phoenician merchants; of King Midas, whose tomb was adorned with treasures; and of the Bible, whose stories are illuminated by recent artistic and archaeological discoveries. It was also a time of rich cultural exchange across the Mediterranean and Near East as diverse populations interacted through trade, travel and migration. This book showcases masterpieces that reflect the cultural encounters of this era. Stunning details convey the significance of more than 300 objects drawn from collections around the globe. These objects include carved reliefs from the majestic palaces of ancient Assyria, Phoenician fine bronze metalwork and carved ivories, Egyptian statues, and luxurious jewelry. Texts by over 80 international scholars provide a compelling picture of this fascinating period, one that is essential to understanding the origins of Western culture and art." -- Publisher's website.